The guidebook for performance improvememt : working with individuals and organizations - Kaufman, Roger A.; Thiagarajan, Sivasailam; MacGillis, Paula (San Francisco, CA : Pfeiffer, 1997)
The ultimate resource for improvement and planning! This treasure trove of information gives you expert direction for helping your organization and its employees improve performance. Unlike most resources on organizational improvement that consider only the micro- (individual) and macro- (organization) levels, this guide incorporates the mega- (customer/client) level in planning success.
Includes bibliographical references and index.
oif 11/09/14
Loan
Keywords: Organizational effectiveness; Performance